Development of the Smartphone-Based Edutainment Game “MathVenture” as a Learning Medium Oriented Towards Creative Thinking Skills - Hermansyah, Hermansyah; Widyawati, Eka (Insitut Agama Islam Negeri Kerinci, 2024)
This study aims to develop and evaluate MathVenture, a smartphone-based educational game designed to enhance students' creative thinking and engagement in mathematics learning. The development process followed the ADDIE model, consisting of five phases: Analysis, Design, Development, Implementation, and Evaluation. The study involved 30 students and 10 teachers from a Junior High School. Data were collected through pre- and post-tests to assess students' creative thinking, as well as questionnaires to evaluate the practicality of the game from both students' and teachers' perspectives. The pre-test and post-test results showed a significant increase in students' creative thinking scores, with an average pre-test score of 8.0 and a post-test score of 13.0 (t = 5.00, p < 0.05). The game received high usability ratings, with the teachers' average score for practicality being 4.29 (Very Good), and the students' average score being 4.82 (Very Good). The study concludes that MathVenture is an effective tool for enhancing creative thinking and student motivation in mathematics learning, contributing to the growing body of research on game-based learning in education.